THE PHENOMENON OF COMMUNICATIVE CULTURE IN THE INFORMATION SOCIETY - Antipova, Olga (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2025)
The characteristics of the information era make it possible to state dynamic and radical changes in communicative interaction, which is primarily related to the high rank in the hierarchy of information values. The aim and tasks of the article are to understand the communicative characteristics of the information society through the prism of the sociocultural component. Research methods. The methodological toolkit relies on philosophical-anthropological, hermeneutic, and socio-cultural approaches. Research results. It is proved that the phenomenon of communicative culture from a factor that accompanies the process of social interaction turns into one of the leading factors of achieving social stability and orderliness due to its stabilizing effect on communicative processes. At the same time, in the context of informatization, communication faces growing challenges, as manipulative technologies and emotionally charged content, such as fake news, viral slogans, and memes, increasingly dominate, leading to the dehumanization of discourse, the rise of "decommunication," and the erosion of genuine understanding in favor of controlled narratives shaped by states, corporations, and other agents of influence. Discussion. The analysis of the communicative characteristics of the modern cultural age in the context of informatization complements the conceptual achievements of theorists in formalized issues. This analysis aims to identify positive and negative trends of means of communication in modern conditions. Conclusions. In the information era, communicative culture takes on an ambivalent character: on the one hand, it involves a more flexible toolkit for creating information products, while on the other, it is accompanied by numerous risks that demand information literacy from the subjects of interaction